Impact of pathological response after neoadjuvant chemotherapy on adjuvant therapy decisions and patient outcomes in gastrointestinal cancers. Issue 6 (25th May 2021) - Bhalla, Sheena; Zhu, Huili; Lin, Jung‐Yi; Özbek, Umut; Wilck, Eric J.; Chang, Sanders; Chen, Xiuxu; Ward, Stephen; Harpaz, Noam; Polydorides, Alexandros D.; Miller, William; Fiel, Maria Isabel; et al.
Abstract: Background: Neoadjuvant chemotherapy (NAC) is frequently used in gastrointestinal cancers (GIC), and pathological, radiological, and tumor marker responses are assessed during and after NAC. Aim: To evaluate the relationship between pathologic, radiologic, tumor marker responses and recurrence‐free survival (RFS), overall survival (OS), adjuvant chemotherapy (AC) decisions, and the impact of changing to a different AC regimen after poor response to NAC. Methods and results: Medical records of GIC patients treated with NAC at Mount Sinai between 1/2012 and 12/2018 were reviewed. One hundred fifty‐six patients (58.3% male, mean age 63 years) were identified. Primary tumor sites were: 43 (27.7%) pancreas, 62 (39.7%) gastroesophageal, and 51 (32.7%) colorectal. After NAC, 31 (19.9%) patients had favorable pathologic response (FPR; defined as College of American Pathologists [CAP] score 0–1). Of 107 patients with radiological data, 59 (55.1%) had an objective response, and of 113 patients with tumor marker data, 61 (54.0%) had a ≥50% reduction post NAC. FPR, but not radiographic or serological responses, was associated with improved RFS (HR 0.28; 95% CI 0.11–0.72) and OS (HR 0.13; 95% CI 0.2–0.94). Changing to a different AC regimen from initial NAC, among all patients and specifically among those with unfavorable pathological response (UPR; defined as CAP score 2–3) after NAC, was not associated with improved RFS or OS. Conclusions: GIC patients with FPR after NAC experienced significant improvements in RFS and OS. Patients with UPR did not benefit from changing AC. Prospective studies to better understand the role of pathological response in AC decisions and outcomes in GIC patients are needed.